Bad faith and unreasonableness as grounds for civil-legal liability of a person functioning as a sole executive body of an economic entity - E. B. Abakumova (Russian Journal of Economics and Law)
Objective: theoretical and legal analysis of the application of the legal categories of good faith and reasonableness in judicial practice on corporate disputes related to bringing directors of companies to civil liability.Methods: the work used general (system approach, analysis, synthesis, induction, deduction) and special legal (formal legal, comparative legal) methods.Results: based on the study of the Russian legislation and law enforcement practice, the article analyzes the theoretical and practical issues of bringing to civil liability the heads of enterprises for losses caused to the company as a result of unfair or unreasonable actions committed by them. The paper focuses on the foreign experience in the field under study and reveals the relationship of the Russian terms “good faith” and “reasonableness” with the fiduciary duty of a manager to be loyal to the corporation and to take due care of the owner’s interests.Scientific novelty: the author reveals the theoretical and legal meaning of the concepts of “good faith” and “reasonableness” in corporate relations, which does not coincide with the general civil understanding of these legal categories. The paper substantiates the fundamental importance of determining the legal meaning of the term “interests of a legal entity” forjudicial practice in cases of bringing to justice persons who perform the functions of executive bodies of business entities. The article proposes to set out Part 3 of Article 53 of the Russian Civil Code as follows: “a person, by virtue of the law or any other legal act or constitutive documents of the legal entity, authorized to act on its behalf must act in accordance with the objectives and interests of the legal entity they represent, reasonably and in good faith”. This clarification assumedly will reduce the uncertainty in conflict situations that arise regarding the assessment of the director’s actions compliance with the legal entity interests. This wording clearly shows that, regardless of the current interests of the business entity expressed, for example, by the general meeting of participants, the director should first of all be guided by the goals of the legal entity when making any decision.Practical significance: the main provisions and conclusions of the work can be used in scientific, pedagogical and law enforcement activities when considering issues related to the civil liability of directors in cases where their actions require correlation with the legal entity interests.